PENGARUH INTELLECTUAL CAPITAL DAN CORPOEATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA - Bettri Mistari; Rindah Mustika; Maya Panorama; Qasiratut Tharfi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
The purpose of this study was to analyze and determine the effect of Intellectual Capital and Good Corporate Governance on the financial performance of banking companies listed on the Indonesia Stock Exchange. The research population is all banking companies listed on the Indonesia Stock Exchange 2015-2021 as many as 47 companies. The number of samples that meet the criteria are 23 companies with 7 years of observation. The analysis technique used in this research is multiple linear regression. The R-Square value is 69.4%. This shows that the independent variable has an influence on the financial performance of banking companies listed on the Indonesia Stock Exchange by 69.4 while 30.6% is influenced by other variables outside this research model. The results of the t test show that the Intellectual Capital variable has a significant positive effect on financial performance, and Good Corporate Governance has an insignificant negative effect on financial performance. While the F test simultaneously has a positive and significant effect on financial performance.